Dexmedetomidine reduces the neuronal apoptosis related to cardiopulmonary bypass by inhibiting activation of the JAK2–STAT3 pathway - Chen Y; Zhang X; Zhang B; He G; Zhou L; Xie Y (Dove Medical Press, 2017)
Yanhua Chen,1,* Xu Zhang,2,* Bingdong Zhang,1 Guodong He,2 Lifang Zhou,2 Yubo Xie2 1Department of Anesthesiology, Cardiovascular Institute, 2Department of Anesthesiology, the First Affiliated Hospital of Guangxi Medical University, Nanning, China *These authors contributed equally to this work Abstract: Cardiopulmonary bypass (CPB) constitutes one of the primary methodologies pertaining to cardiac surgery. However, this form of surgery can cause damage to the body. Many studies have reported that dexmedetomidine confers cerebral protection. In this study, we aimed to investigate the effect and mechanism of dexmedetomidine on neuronal apoptosis caused by CPB. Here, rats were treated with different doses of dexmedetomidine by intravenous infusion 2 hours after CPB. We observed that dexmedetomidine treatment to rats reduces the S100ß, NSE levels in plasma, and neuronal apoptosis following CPB in a dose-dependent manner. Furthermore, we observed that the beneficial effect of dexmedetomidine treatment following CPB was associated with a reduction in IL6, an inflammatory cytokine in plasma and cortex. Our results suggest that dexmedetomidine provides neuroprotective effects by inhibiting inflammation and reducing neuronal apoptosis. There was a correlation between the protective effect on the brain and the dose of dexmedetomidine. In addition, dexmedetomidine administration inhibits phosphorylation of JAK2 and STAT3 proteins in the hippocampus of rats 2 hours after CPB. Therefore, we speculate that the JAK2–STAT3 pathway plays an important role in the neuroprotective effects of dexmedetomidine following brain injury induced by CPB. Keywords: apoptosis, cardiopulmonary bypass, dexmedetomidine, neuroprotective effect, JAK2, STAT3